Hemotherapy algorithm for the management of trauma-induced coagulopathy: the German and European perspective. Issue 2 (April 2017) - Maegele, Marc; Nardi, Giuseppe; Schöchl, Herbert
Abstract : Purpose of review: This review presents a synopsis of best current knowledge with reference to the updated German and European guidelines and recommendations on the management of severe trauma hemorrhage and trauma-induced coagulopathy as well as a viscoelastic-based treatment algorithm based upon international expert consensus to trigger the administration of hemostatic agents and blood products. Recent findings: Uncontrolled hemorrhage and trauma-induced coagulopathy are the major causes for preventable death after trauma and early detection and aggressive management have been associated with improved outcomes. However, best practice to treat this newly defined entity is still under debate. In the acute phase, the clinical management usually follows the 'Damage Control Resuscitation' concept, which advocates the empiric administration of blood products in predefined and fixed ratios. As an alternative, several European but also a few US trauma centers have instituted the concept of 'Goal-directed Coagulation Therapy' based upon results obtained from early point-of-care viscoelastic testing. Summary: Current guidelines urge for the implementation of evidence-based local protocols and algorithms including clinical quality and safety management systems together with parameters to assess key measures of bleeding control and outcome.